Efektifitas Pengendalian Banjir dengan Embung: Studi Kasus Taman Firdaus Universitas Sriwijaya - Deny Ferdian; Anis Saggaff; Sarino (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2020)
Flood is triggered by a decrease in catchment areas due to an increase in population, activities, and land requirements, both for settlements and economic activities. The flood occurs annually during the wet season at downstream of the campus of Sriwijaya University. In 2019, the downstream swampy land of about 100 ha was excavated and functioned as a retention basin or small reservoir called Embung. The reservoir at Taman Firdaus, Sriwijaya University, was designed by using spillway's top elevation at +5.00m. The objective of the research was to analyze the effectivity of the reservoir on the flood water level of the Kelekar river. One dimensional modelling was used to model the hydraulic routing through small reservoir and Kelekar river. Based on the results of the modeling, it can be seen that the reservoir at Taman Firdaus Universitas Sriwijaya could hold water as much as 1.446.409,39 m3, and lower the flood water level in the Kelekar River by approximately 1 to 1.5 meters.